Influence of Migration on Populational and Regional Development Introduction - Śaśek, Miroslav (Wpływ procesów migracyjnych na ludność i rozwój regionalny, 2008)
This contribution continues with the topic the author dealt with in contributions read in recent years in conferences in Ústí nad Labem and Jelenia Góra. In the theoretical part the author tries to describe the links between migration and populational and regional development. In the analytical part the author continues in migration development observation and in observation of its influence on populational development, especially within the transformation period of the most important cities and towns of the Czech Republic. (excerpt from the text)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 268-277